Effects of expertise on football betting - Khazaal Yasser; Chatton Anne; Billieux Joël; Bizzini Lucio; Monney Grégoire; Fresard Emmanuelle; Thorens Gabriel; Bondolfi Guido; El-Guebaly Nady; Zullino Daniele; Khan Riaz (BMC, 2012)
Abstract Background Football (soccer) is one of the most popular sports in the world, including Europe. It is associated with important betting activities. A common belief, widely spread among those who participate in gambling activities, is that knowledge and expertise on football lead to better prediction skills for match outcomes. If unfounded, however, this belief should be considered as a form of "illusion of control." The aim of this study was to examine whether football experts are better than nonexperts at predicting football match scores. Methods Two hundred and fifty-eight persons took part in the study: 21.3% as football experts, 54.3% as laypersons (non-initiated to football), and 24.4% as football amateurs. They predicted the scores of the first 10 matches of the 2008 UEFA European Football Championship. Logistic regressions were carried out to assess the link between the accuracy of the forecasted scores and the expertise of the participants (expert, amateur, layperson), controlling for age and gender. Results The variables assessed did not predict the accuracy of scoring prognosis (R2 ranged from 1% to 6%). Conclusions Expertise, age, and gender did not appear to have an impact on the accuracy of the football match prognoses. Therefore, the belief that football expertise improves betting skills is no more than a cognitive distortion called the "illusion of control." Gamblers may benefit from psychological interventions that target the illusion of control related to their believed links between betting skills and football expertise. Public health policies may need to consider the phenomenon in order to prevent problem gambling related to football betting.